2021
DOI: 10.1186/s40066-020-00277-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate smart agriculture on household welfare in smallholder integrated crop–livestock farming systems: evidence from Zimbabwe

Abstract: Background Agriculture contributes significantly to the welfare of smallholder farmers, but it has become highly susceptible to climate change, due to its reliance on the increasingly erratic rainfall patterns. Climate Smart Agriculture (CSA) offers important opportunities for enhancing food security and incomes through increased agriculture productivity. Technology evaluation through impact studies provides information on the effect of CSA on farmer welfare, thereby highlighting its potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 60 publications
(86 reference statements)
5
13
0
Order By: Relevance
“…which undoubtedly could assist in rice production and in responding to the changing climate in the area. This is also related to the findings of Abegunde et al [40] and Mujeyi et al [41]. The majority (65%) of the farmers were males.…”
Section: Socio-economic Characteristics Of the Farmerssupporting
confidence: 83%
“…which undoubtedly could assist in rice production and in responding to the changing climate in the area. This is also related to the findings of Abegunde et al [40] and Mujeyi et al [41]. The majority (65%) of the farmers were males.…”
Section: Socio-economic Characteristics Of the Farmerssupporting
confidence: 83%
“…The findings, as highlighted in Table 4 show that, the adoption of blended improved sorghum seed and partialorganic fertilizer CSA technology has a significant effect on both the productivity and household income of the adopting households. This result concurs with other studies, which also reported the gains from adoption of the different dimensions of CSA adoption (Musara and Musemwa, 2020;Mujeyi et al, 2021). As reported by Ghimire and Huang (2015) in Nepal, farmers who adopted improved maize varieties generated household wealth as opposed to the non-adopting counterparts.…”
Section: Resultssupporting
confidence: 92%
“…As reported by Ghimire and Huang (2015) in Nepal, farmers who adopted improved maize varieties generated household wealth as opposed to the non-adopting counterparts. A study by Mujeyi et al (2021) on the impact of CSA on household welfare in smallholder integrated crop-livestock farming systems also confirmed a robust relationship between food security, income and CSA adoption. It therefore shows that, the CSA interventions implemented in the smallholder farming societies have the potential to support gains among the adopting households in various dimensions including productivity and income.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations